2021
DOI: 10.3390/jcm10163474
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Incidence and Outcomes of Patients Hospitalized by Idiopathic Pulmonary Fibrosis (IPF) in Spain from 2016 to 2019

Abstract: (1) Background: To assess sex differences in the incidence, characteristics, procedures and outcomes of patients admitted with idiopathic pulmonary fibrosis (IPF); and to analyze variables associated with in-hospital mortality (IHM). (2) Methods: We analyzed data collected by the Spanish National Hospital Discharge Database, 2016–2019. (3) Results: We identified 13,278 hospital discharges (66.4% men) of IPF (primary diagnosis 32.33%; secondary diagnosis: 67.67%). Regardless of the diagnosis position, IPF incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
0
1
Order By: Relevance
“…In agreement with recent observations [ 44 , 59 ], survival was not significantly associated with sex; however, this is in contrast with other studies in which the female sex was significantly associated with a lower risk of in-hospital mortality [ 60 , 61 ]. Moreover, in contrast with other reports [ 62 , 63 ], age was not independently associated with survival. However, it should also be highlighted that this observation is in line with other studies [ 64 , 65 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In agreement with recent observations [ 44 , 59 ], survival was not significantly associated with sex; however, this is in contrast with other studies in which the female sex was significantly associated with a lower risk of in-hospital mortality [ 60 , 61 ]. Moreover, in contrast with other reports [ 62 , 63 ], age was not independently associated with survival. However, it should also be highlighted that this observation is in line with other studies [ 64 , 65 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have also found a worse course of disease in male patients than female patients with ILDs. 1,7,8 Based on pharmacokinetic studies in patients with IPF, age, bodyweight, smoking, and Asian race influence nintedanib exposure, within the range of interpatient variability. 25,26 Further analyses of data from patients with various ILDs showed a positive association between nintedanib exposure and the risk of liver enzyme elevations.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The most common ILD, idiopathic pulmonary fibrosis (IPF), is more common in men than women. 7 Studies in patients with various ILDs have found male sex to be associated with more severe ILDs than female sex, as indicated by increased lung function impairment and increased risk of mortality. 7,8 Nintedanib is a tyrosine kinase inhibitor that inhibits processes fundamental to the progression of pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation